Perceptions and Attitudes of Students towards the Benefits of Forests at ETCI Ermera Campus - Leopoldino Vasco Martins; Luis Pereira (International Journal of Integrative Sciences, 2024)
The objectives to be achieved in this study are to determine the perception and attitude of students towards the benefits of urban forests in Talimoro Village. The variables observed in this study were student’s perceptions and attitudes towards the benefits of urban forests. The determination of the sample carried out was 3 faculties and 10 departments getting 10 respondents so that the total number was 100 respondents. The data collection method was carried out by taking secondary data and direct observation in the field. The collected data were analysed using the SPSS application to determine the frequency of students' perceptions and attitudes. The results showed that East Timor Coffee Institute students had a Very Good perception, with a score of 447 and statements regarding personal experiences from 100 respondents had a very good attitude with a score of 388.